Lola Plants a Garden - McQuinn, Anna; Beardshaw, Rosalind (Watertown, MA : Charlesbridge, 2014)
Lola plants a flower garden with her parent's help, and watches it grow.
Keywords: Flower gardening -- Juvenile fiction; African American girls -- Juvenile fiction; African American families -- Juvenile fiction; Flower gardening -- Fiction; Gardening -- Fiction; African Americans -- Fiction; Family life -- Fiction